Test-retest reliability and validity of distortion product oto-acoustic emissions and transient evoked oto-acoustic emissions in normal hearing adults - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2017)
Dissertation (MCommunication Pathology)--University of Pretoria, 2017.